Thrombophilia in non‐thrombotic chronic venous disease of the lower limb – a systematic review. (28th November 2018) - Tan, Matthew K. H.; Onida, Sarah; Laffan, Michael; Davies, Alun H.
Summary: Chronic venous disease (CVD) represents a significant healthcare burden. Thrombophilia is proposed as a risk factor, particularly for post‐thrombotic CVD. A systematic review was performed to determine the relationship between thrombophilia and non‐thrombotic CVD. MEDLINE ® and Embase ® databases were searched from 1946 up to March 2018. Case‐control studies, cohort studies or randomised clinical trials reporting on thrombophilias in non‐thrombotic lower limb CVD in adult patients were included. Non‐English and post‐thrombotic syndrome studies were excluded. Study selection and data extraction were performed by two reviewers. Fifteen studies were included, reporting on 916 cases and 1261 controls. Studies largely focused on venous ulceration and investigated multiple haemostatic factors. An association between thrombophilia and non‐thrombotic CVD was identified, with greater prevalence and factor concentration alteration reported in patients compared to controls. Concomitant thrombophilia presence was associated with earlier CVD onset. Relationship strength varied, with commoner aetiologies showing clearer correlation than rarer ones. Thrombophilia is associated with non‐thrombotic CVD but the mechanism is unclear and causation cannot be determined. Future research should focus on prospective studies with larger populations and identify adjunct therapies targeting thrombophilia.